LEARNING EXPERIENCES OF STUDENTS ABOUT ONLINE TEACHING AND LEARNING DURING COVID-19 PANDEMIC IN BALOCHISTAN - Siraj Bashir; Ghulam Murtaza; Sana Ullah; Mobeen Ahmed; Shakir Adam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Public and private universities around the world are closed because of the COVID-19, nearly one billion students have had their education interrupted and moved their educational activities onto the online platform. The purpose of this research study is to know the impact, issues, and tools of online-teaching during COVID-19 at the higher education levels of Balochistan. An online survey was conducted in which the students from four universities namely, University of Balochistan, Sardar Bahadar Khan Women's University, BUITEMS University and University of Turbat were asked about their opinion on online teaching and learning during the ongoing pandemic. The data, collected by questionnaire, were analyzed, using percentage and frequency. The results of the study exposed that the universities in Balochistan were not prepared for online teaching classes. It was observed that online teaching played a key role during COVID-19, but lack of resources, access to the internet availability, and proper use were the major issues during online-teaching in Balochistan. The findings of the study recommended that the technology and online-based teaching should be fully enhanced throughout the province for such pandemic and sudden crises.